The Development of Methodological Framework in Redefining Discourse of Malaysia Architecture Identity - Sabil, Azmal Bin; Utaberta, Nangkula; Asif, Nayeem (Penerbit UTHM, 2021)
The ideas in adapting Malay tradit ional architecture values have been gazened as one of the resolutions for National Architeccure Idemity as presemed in 'Seminar Ke Arah fdentiti Kebangsaan Dalam Seni Bina' in 1981. Despite the encouragemem from the governmem, th e adaptation of Malay tradicional arch itecmre va lues to the des ign of the modern building are still small in numbers. On top of these small numbers, just a few of them are considered appropriately transformed. Based on this prolong issues, this paper anempts to redefine the direction of the long debates of National Architecture Idemity discourse by proposing the new paradigm and methodological framework. T he new objectives are constructed from the Malaysia modern comemporary architeccure ideas and thoughts, recem publica tion s and public forums which discussing the issues on National Architecture Idemity. On the methodological framework, the research onion methodologies are adapted.